Tunnel Back Analysis Based on Differential Evolution Using Stress and Displacement - Joon-Sang An; Kyung-Nam Kang; Ju-Young Choi; Won-Suh Sung; Vathna Suy; Ki-Il Song (Advances in Civil Engineering)
The stability of tunnels has mainly been evaluated based on displacement. Because displacement due to the excavation process is significant, back analysis of the structure and ground can be performed easily. Recently, the length of a segment-lined tunnel driven by the mechanized tunneling method is increasing. Because the internal displacement of a segment-lined tunnel is trivial, it is difficult to analyze the stability of segment-lined tunnels using the conventional method. This paper proposes a back analysis method using stress and displacement information for a segment-lined tunnel. A differential evolution algorithm was adopted for tunnel back analysis. Back analysis based on the differential evolution algorithm using stress and displacement was established and performed using the finite difference code, FLAC3D, and built-in FISH language. Detailed flowcharts of back analysis based on DEA using both monitored displacement stresses were also suggested. As a preliminary study, the target variables of the back analysis adopted in this study were the elastic modulus, cohesion, and friction angle of the ground. The back analysis based on the monitored displacement is useful when the displacement is significant due to excavation. However, the conventional displacement-based back analysis is unsuitable for a segment-lined tunnel after construction because of its trivial internal displacement since the average error is greater than 32% and the evolutionary calculation is finalized due to the maximum iteration criteria. The average error obtained from the proposed back analysis algorithm using both stress and displacement ranged within approximately 6–8%. This also confirms that the proposed back analysis algorithm is suitable for a segment-lined tunnel.